Characterization of extracellular polymeric substances and microbial diversity in anaerobic co-digestion reactor treated sewage sludge with fat, oil, grease. (July 2016) - Yang, Zhao-Hui; Xu, Rui; Zheng, Yue; Chen, Ting; Zhao, Li-Jun; Li, Min
Highlights: Two anaerobic co-digesters of sewage sludge and fat, oil, grease operated 180d. Fat, oil, grease addition enhanced anaerobic co-digestion performance significantly. Sequencing technology comprehensively revealed the dynamic change of microbial communities. Co-digestion simulated the degradation of extracellular polymeric substances. Abstract: Performance of co-digesters, treated of sewage sludge (SS) with fat, oil and grease (FOG), were conducted semi-continuously in two mesophilic reactors over 180 days. Compared with SS mono-digestion, biogas production and TS removal efficiency of co-digestion were significantly enhanced up to 35% and 26% by adding upper limit FOG (60% on VS). Enhancement in co-digestion performance was also stimulated by the release of extracellular polymeric substances (EPS), which was increased 40% in both loosely bound EPS (LB-EPS) and tightly bound EPS (TB-EPS) than that of mono-digester. Based on high-throughput sequencing (HTS), analysis of microbial 16S rRNA gene comprehensively revealed the dynamic change of microbial community. Results showed that both bacterial and archaeal undergone an apparent succession with FOG addition, and large amount of consortium like Methanosaeta and N09 were involved in the process. Redundancy analysis showed the acetoclastic genera Methanosaeta distinctly related with biogas production and EPS degradation.